Temporal patterns in multiple stressors shape the vulnerability of overwintering Arctic zooplankton - Albini Dania; Mathieu Lutier; Martin P. Heimböck; Jan Heuschele; Janne E. Søreide; Michelle C. Jackson; Khuong V. Dinh (Ecology and Evolution)
Abstract The Arctic polar nights bring extreme environmental conditions characterised by cold and darkness, which challenge the survival of organisms in the Arctic. Additionally, multiple anthropogenic stressors can amplify the pressure on the fragile Arctic ecosystems during this period. Determining how multiple anthropogenic stressors may affect the survival of Arctic life is crucial for ecological risk assessments and management, but this topic is understudied. For the first time, our study investigates the complex interactions of multiple stressors, exploring stressor temporal dynamics and exposure duration on a key Arctic copepod Calanus glacialis during the polar nights. We conducted experiments with pulse (intermittent) and press (continuous) exposure scenarios, involving microplastics, pyrene and warming in a fully factorial design. We observed significant effects on copepod survival, with pronounced impacts during later stressor phases. We also detected two‐way interactions between microplastics and pyrene, as well as pyrene and warming, further intensified with the presence of a third stressor. Continuous stressor exposure for 9 days (press‐temporal scenario) led to greater reductions in copepod survival compared to the pulse‐temporal scenario, characterised by two 3‐day stressor exposure phases. Notably, the inclusion of recovery phases, free from stressor exposure, positively influenced copepod survival, highlighting the importance of temporal exposure dynamics. We did not find behaviour to be affected by the different treatments. Our findings underscore the intricate interactions amongst multiple stressors and their temporal patterns in shaping the vulnerability of overwintering Arctic copepods with crucial implications for managing Arctic aquatic ecosystems under the fastest rate of ongoing climate change on earth.